From Health Search to Health Care: Explorations of Intention and Utilization via Query Logs and User Surveys - White, Ryen W.; Horvitz, Eric (Journal of the American Medical Informatics Association, 2013)
Objective We seek to better understand the relationship between online health-seeking behaviors and in-world healthcare utilization (HU). We do so via studies of online search and access activities before and after queries that pursue medical professionals and facilities. Materials and Methods We analyze data collected from logs of online searches gathered from consenting users of a browser toolbar from Microsoft (N = 9,740). We employ a complementary survey (N = 489) to seek a deeper understanding of information-gathering, reflection, and action on the pursuit of professional healthcare. Results We provide insights about HU through the survey, breaking out its findings by different respondent marginalizations as appropriate. Observations made from search logs may be explained by trends observed in our survey responses, even though the user populations differ. Discussion The results provide insights about how users decide if and when to utilize healthcare resources, and how online health information seeking transitions to in-world HU. The findings from both the survey and the logs reveal behavioral patterns and suggest a strong relationship between search behavior and healthcare utilization. Although the diversity of our survey respondents is limited and we cannot be certain that users visited medical facilities, we demonstrate that it may be possible to infer HU from long-term search behavior by the apparent influence that health concerns and professional advice have on search activity. Conclusion Our findings highlight different phases of online activities around queries pursuing professional healthcare facilities and services. We also show that it may be possible to infer HU from logs without tracking people’s physical location, based on the effect of HU on pre- and post-HU search behavior. This allows search providers and others to develop more robust models of interests and preferences by modeling utilization rather than simply the intention to utilize that is expressed in search queries.